Managing lives at work: Lessons from Bhagavad Gita - Weerawardena, S.D.; Priyasad, K.P.M.; Weerasinghe, T.D. (University of Jaffna, 2018)
This review of literature critiques the insights manifested in Bhagavad Gita to be applied in modern organizations to effectively manage people at work. A narrative review of relevant articles known to the authors on Bhagavad Gita was conducted. Among the lessons of the Bhagavad Gita, it is found that empowering employees through 'Bakthi', 'Yukthi' and 'Mukthi' lays the foundation stone of effective Human Resource Management (HRM). Further, Bhagavad Gita supports the generally held belief of no one has the right to remain in the society without performing any work. Moreover, to be beneficial for both individual employees and organizations, it is recommended in Gita to nurture a divine work culture (daivisampat) which involves fearlessness, self-control, tolerance of scarification and assertiveness.
Keywords: Human Resource Management, Empowerment; Performance Management; Work Culture